2006
DOI: 10.1093/ejo/cjl053
|View full text |Cite
|
Sign up to set email alerts
|

Anterior open bite treated with a palatal crib and high-pull chin cup therapy. A prospective randomized study

Abstract: The aim of this prospective randomized clinical study was to cephalometrically investigate the dentoalveolar and soft tissue changes produced by a removable appliance with a palatal crib associated with high-pull chin cup therapy in children with an Angle Class I anterior open bite (AOB) malocclusion. Thirty children (8 males and 22 females) with an initial mean age of 8.3 years and a mean AOB of 4.1 mm were treated with a removable appliance composed of a palatal crib associated with chin cup therapy for 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 29 publications
8
63
2
8
Order By: Relevance
“…These findings were similar to those described in a previous short-term study that reported a significantly greater downward rotation (1.2 ) of the palatal plane associated with a significant reduction in the intermaxillary divergence (À1.7 ) in the Q-H/C sample with respect to the controls at the end of the active treatment. 17 On the other hand, our short-term treatment outcomes disagreed with those of Pedrin et al 23 and Torres et al 24 The results of both studies showed that the effects of therapy primarily were dentoalveolar without significant changes in the skeletal maxillary and mandibular components. The initial mean amount of negative overbite (a measure of anterior dentoalveolar open bite) was À3.3 mm in the Q-H/C group.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…These findings were similar to those described in a previous short-term study that reported a significantly greater downward rotation (1.2 ) of the palatal plane associated with a significant reduction in the intermaxillary divergence (À1.7 ) in the Q-H/C sample with respect to the controls at the end of the active treatment. 17 On the other hand, our short-term treatment outcomes disagreed with those of Pedrin et al 23 and Torres et al 24 The results of both studies showed that the effects of therapy primarily were dentoalveolar without significant changes in the skeletal maxillary and mandibular components. The initial mean amount of negative overbite (a measure of anterior dentoalveolar open bite) was À3.3 mm in the Q-H/C group.…”
Section: Discussioncontrasting
confidence: 88%
“…This result agrees with the outcome at the end of active therapy with the same treatment protocol reported in a previous short-term study. 17 Similarly, in the short-term results of Pedrin et al, 23 the treated group showed a significant closure of the anterior open bite of 5.0 mm, whereas Torres et al 24 found an improvement in overbite of 3.9 mm. In our study, a statistically significant lingual tipping (À3.7 ) of the mandibular incisors to the mandibular plane contributed to the correction of overbite in the Q-H/C group.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ferreira-Pedrin et al 14 and Torres et al 29 evidenced the retroclination of these same teeth, due to the difficulty of tongue contact promoted by the palatal crib, therefore making the lower lip act more strongly on these teeth. This action promoted a statistical significant retroclination of these teeth during the use of the appliance, therefore, treatment provided an improvement in lip sealing.…”
Section: Changes Comparisons Between Groupsmentioning
confidence: 94%
“…(ELLIS et al, 1985;FERREIRA-PEDRIN et al, 2006;JANSON et al, 2003;TORRES et al, 2006, CREPALDI, 2008 Como constatado no estudo de Ferreira-Pedrin et al (2006) apresentou uma melhora espontânea do trespasse vertical e finalizou com -1mm, sem correção da má oclusão.…”
Section: Alguns Autores Avaliando O Tratamento Da Mordida Aberta Anteunclassified